PENGARUH PENGGUNAAN MODEL TWO STAY TWO STRAY TERHADAP HASIL BELAJAR IPS SISWA DI SD - Khumairah, Siti; Marli, Suhardi; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to find out how much influence the use of Two Stay Two Stray model to the learning outcomes of IPS students of class III SDN 34 Pontianak City